2022
DOI: 10.1021/acs.jpcb.2c03930
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Research of Spatial Orientation and Kinetic Energy of Active Site Collision of Carnosine under Weak Microwave Irradiation

Abstract: The molecular mechanism of the microwave nonthermal effect is still not clear. This work investigated the spatial orientation and kinetic energy of active site collision of carnosine, a natural bioactive dipeptide, under the weak microwave irradiation using the molecular dynamics simulation. Our results showed the influences of the temperature, microwave intensity, microwave frequency, and microwave polarization mode (linear polarization and circular polarization) on the spatial orientation and kinetic energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…This study sheds light on the relationship between several MW parameters, such as the output watts, and several mineralization peptide parameters, such as the amount of precipitation. In future studies, we will use computational chemistry to investigate the direct relationship among MWs, peptide sequences and mineralization 25 , 26 and compare them to wet experimental results. Our findings may aid in the treatment of teeth and bones and the development of organic–inorganic nanobiomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…This study sheds light on the relationship between several MW parameters, such as the output watts, and several mineralization peptide parameters, such as the amount of precipitation. In future studies, we will use computational chemistry to investigate the direct relationship among MWs, peptide sequences and mineralization 25 , 26 and compare them to wet experimental results. Our findings may aid in the treatment of teeth and bones and the development of organic–inorganic nanobiomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…The microwave "non-thermal effect" could be understood as the microwave polarization effect on the spatial orientation and the high kinetic energy of reactive site collision, thus increasing the effective probability of molecules and reducing the chemical reaction activation energy. 69,70 This means that the DRM process in the microwave eld can be carried out with faster rate at a lower temperature. It could also be observed that the H 2 /CO ratio of MW-DRM process is higher than that of the conventional heating, which could be explained by the promotion of methane decomposition reaction under microwave irradiation due to the locally enhanced temperature caused by "hotspots" and plasma.…”
Section: Microwave-induced Dry Reforming Of Methane (Mw-drm) Processmentioning
confidence: 99%